2017
DOI: 10.1111/bjep.12145
|View full text |Cite
|
Sign up to set email alerts
|

Explaining academic‐track boys’ underachievement in language grades: Not a lack of aptitude but students’ motivational beliefs and parents’ perceptions?

Abstract: Our results challenge the stereotypic belief that boys' lower grades are due to lower verbal aptitude. Rather, students' motivational beliefs and parents' perceptions seem critical factors. Implications for both future research and practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 82 publications
3
24
0
4
Order By: Relevance
“…These findings highlight that male students’ motivational deficits in foreign language study are partially rooted in their socially acquired masculine identities. Since previous studies have shown that male students’ underachievement in language classes is probably due to a lack of motivation but not a lack of aptitude (Heyder, Kessels, & Steinmayr, 2017), our results provide additional support for the importance of social psychological mechanisms for men’s achievement in this domain.…”
Section: Discussionsupporting
confidence: 77%
“…These findings highlight that male students’ motivational deficits in foreign language study are partially rooted in their socially acquired masculine identities. Since previous studies have shown that male students’ underachievement in language classes is probably due to a lack of motivation but not a lack of aptitude (Heyder, Kessels, & Steinmayr, 2017), our results provide additional support for the importance of social psychological mechanisms for men’s achievement in this domain.…”
Section: Discussionsupporting
confidence: 77%
“…A variety of empirical studies has found that girls' ability self-concept and intrinsic motivation in math were significantly lower than boys' (e.g., Watt 2006) although gender differences in average math achievement (e.g., Else-Quest et al 2010) or the perceived usefulness of math (e.g., Watt 2006) were relatively weak or nonexistent. In the verbal domain, by contrast, boys reported a lower ability self-concept (e.g., Heyder et al 2017) and lower intrinsic motivation (e.g., Durik et al 2006) than girls which is in line with their lower reading competencies (e.g., Reilly et al 2019) or language grades (e.g., Heyder et al 2017). Supporting EVT, these gender differences in domain-specific motivation evolved into substantial gender differences in career aspiration and choices, like course-choices in high school (e.g., Wang and Degol 2013), career goals, and career attainment later on (e.g., Lauermann et al 2017).…”
Section: Gender Differences In Math and Language Motivationmentioning
confidence: 98%
“…Esta posición se revela como un tema polémico a nivel epistemológico, político y social, ya que cuestiona la validez científica del conocimiento en el cual se sustenta, critica las políticas y medidas que se han generado con base en el diagnóstico construido y, finalmente, invalida el panorama social y de género (Griffin, 2008;Heyder et al, 2017).…”
Section: Introductionunclassified